2019
DOI: 10.7759/cureus.4516
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Perforation Secondary to Enteric Fever: An Interesting Case of Acute Abdomen

Abstract: Enteric fever is a common infectious disease, especially in countries with poor sanitation and in the tropics. It is caused mainly by Salmonella typhi and accounts for nearly 27 million cases worldwide and 200,000 deaths annually. Enteric fever involves the reticuloendothelial system such as bone marrow, spleen, and liver. As it mostly involves the Peyer’s patches of the terminal ileum, enteric perforation occurs commonly. However, gallbladder perforation can also occur, though not very often. Ultrasound as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Acute acalculous cholecystitis which causes the gallbladder perforation in pediatric typhoid fever is not extremely rare, but late presentation in patient may become a pitfall in preoperative diagnosis because of the sign of peritonitis mimicking other causes of peritonitis, such as perforation caused by appendicitis which is the most cause of acute abdominal pain in children [4,6]. In this patient, we found type 2 perforated gallbladder based on Niemeier's classification (Table 1).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Acute acalculous cholecystitis which causes the gallbladder perforation in pediatric typhoid fever is not extremely rare, but late presentation in patient may become a pitfall in preoperative diagnosis because of the sign of peritonitis mimicking other causes of peritonitis, such as perforation caused by appendicitis which is the most cause of acute abdominal pain in children [4,6]. In this patient, we found type 2 perforated gallbladder based on Niemeier's classification (Table 1).…”
Section: Discussionmentioning
confidence: 76%
“…It accounts for nearly 27 million cases worldwide and 200000 deaths per year, while in Indonesia the prevalence is 0.3-3%, with highest incidence found in East Java based on 2007. Indonesian Health Research [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study titled gallbladder perforation secondary to enteric fever by N Malik et al (1) concluded that patients with signs and symptoms of typhoid fever along with enteric perforation, gall bladder perforation should be carefully looked for. Typhoid was diagnosed based on IgG and IgM Typhoid tests and the patient did not have bacteraemia.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric fever is a common in tropical countries. It is caused mainly by Salmonella typhi and accounts for nearly 27 million cases worldwide and 200,000 deaths annually (1) . Enteric fever involves the reticuloendothelial system such as bone marrow, spleen, and liver.…”
Section: Introductionmentioning
confidence: 99%